STRESS AND COPING STYLES IN OLDER ADULTS: A COMPARATIVE STUDY IN ARGENTINE INSTITUTIONALIZED AND FREE LIVING OLDER ADULTS - Stefani, Dorina; Feldberg, Carolina (Anales de Psicología / Annals of Psychology, 2006)
Using the Lazarus and Folkman’s transactional approach to stress this study examined the probably effect of elders’ living environment on 1) the situations perceived as potentially threatening and 2) the coping strategies used to lower the perceived threatening . An ex post facto-comparison group design was used. 315 older adults of middium socio-economic level, living in Buenos Aires city, Argentine, were interviewed. They hadn’t cognitive and physical desabilities. Participants completed a socio-demographic questionnaire and a reduced version of 36 items from Lazarus and Folkman coping styles questionnaire (Ways of Coping Checklist -WCCL-). χ2 and MANOVA methods were used to analize the set of data. Results indicated that: older adults who live at their homes in comparison with those who live in nursing homes, had tried to reevaluate the situation in terms to modified the significance and importance of the problem and they have decided to do concrete actions to solve difficulties and to compensate the situation seeking for alternative gratifications. To end, older adults who live in their own houses, tend to keep their affective balance through resignation and through religious believes, which both are external attribution coping style strategies. They also tend to express the discomfort produced by the situation.